Regulation of body length and bone mass by Gpr126/Adgrg6 - Sun, Peng (Sci Adv, 2020)
Adhesion G protein–coupled receptor G6 (Adgrg6; also named GPR126) single-nucleotide polymorphisms are associated with human height in multiple populations. However, whether and how GPR126 regulates body height is unknown. In this study, we found that mouse body length was specifically decreased in Osx-Cre;Gpr126(fl/fl) mice. Deletion of Gpr126 in osteoblasts resulted in a remarkable delay in osteoblast differentiation and mineralization during embryonic bone formation. Postnatal bone formation, bone mass, and bone strength were also significantly affected in Gpr126 osteoblast deletion mice because of defects in osteoblast proliferation, differentiation, and ossification. Furthermore, type IV collagen functioned as an activating ligand of Gpr126 to regulate osteoblast differentiation and function by stimulating cAMP signaling. Moreover,the cAMP activator PTH(1–34), could partially restore the inhibition of osteoblast differentiation and the body length phenotype induced by Gpr126 deletion.Together, our results demonstrated that COLIV-Gpr126 regulated body length and bone mass through cAMP-CREB signaling pathway.